Measurements and Instrumentation - Bakshi (Uday A); Bakshi (Ajay V) (Pune, 2007)
Engineering Design
42237a.jpg;42237b.jpg;42237c.jpg;42237d.jpg;42237e.jpg;42237f.jpg;42237g.jpg;42237h.jpg;42237i.jpg;42237j.jpg;42237k.jpg;42237l.jpg;42237m.jpg;42237n.
15
Keywords: Engineering Design